Child labor the role of income variability and access to credit across countries - Dehejia, Rajeev H.; Gatti, Roberta (National Bureau of Economic Research, 2002)
In the absence of developed financial markets, households appear to resort substantially to child labor to cope with income variability. This evidence suggest that policies aimed at increasing households' access to credit could be effective in reducing child labor.
Keywords: Child labor; Credit; Income distribution; Poverty